Microscopic Characterization of Uranium Ore Specimens Using the Peakaboo Analysis Platform. (August 2020) - McIntyre, Stewart; Van Loon, Lisa; Sherry, Nathaniel; Bauer, Michael; Kotzer, Tom; Banerjee, Neil
Abstract: XRF maps of a uranium ore sample have been analyzed using software that allows the graphical spatial correlations of all detected elements to be measured. The association of uranium with arsenic, nickel and cesium was explored; all showed unique finely-granular microscopic patterns that could be used to assist the recovery of uranium and rare earths.